Argumentative Statements in The 2016 Presidential Debates Of The U.S: A Critical Discourse Analysis - Khoirunisa, Andini; Indah, Rohmani Nur (JEELS (Journal of English Education and Linguistics Studies), 2017)
This study investigates the argumentative statements of Hillary Clinton and Donald Trump during the debates. By employing two theories, Van Dijk's Critical Discourse Analysis (CDA) and Toulmin's model of argument, it aims to expose how various ideologies are expressed in the structure of arguments. It uses Toulmin (2003) model of argument to analyze the structures of argumentation during the debates constituting six elements (i.e. claim, data, warrant, backing, qualifier, and rebuttal). While Van Dijk’s framework covering three levels of discourse structure (the meaning, the argumentation and the rhetoric) is used to analyze the reproduction of racism, manipulation, and Islamophobia. The result indicates the discourse of the candidates contributes the reproduction of manipulation by focusing on the positive self-presentation of “us” (civilized) and negative other-presentationof “them” (terrorists) as a mind control of the audience.